2017
DOI: 10.2139/ssrn.2922433
|View full text |Cite
|
Sign up to set email alerts
|

Demand for Off-Grid Solar Electricity Experimental Evidence from Rwanda

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Importantly, the two‐month payment target in the harvest period served as an interest‐free short‐term loan and commitment device. Financing components proved to increase the WTP in similar contexts, for example, for latrines in Cambodia (Ben Yishay et al 2017) and improved cookstoves in Uganda (Levine et al 2018), but not for solar kits in Rwanda (Grimm et al 2018). Private vendors could replicate all this, but it obviously increases transaction costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the two‐month payment target in the harvest period served as an interest‐free short‐term loan and commitment device. Financing components proved to increase the WTP in similar contexts, for example, for latrines in Cambodia (Ben Yishay et al 2017) and improved cookstoves in Uganda (Levine et al 2018), but not for solar kits in Rwanda (Grimm et al 2018). Private vendors could replicate all this, but it obviously increases transaction costs.…”
Section: Discussionmentioning
confidence: 99%
“…This bespeaks a variety of barriers and frictions that make rural market exploration a highly risky endeavor. Vendors in such a market environment would have to price in risks and logistics, leading to rural end‐user prices that exceed urban prices considerably (see also Adams et al 2016; Barriga and Fiala 2018; Grimm et al 2018; Levine et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DRE options, and among them SHSs and smaller‐scale distributed solar systems, already play an important role in Rwanda's electrification efforts and will continue to do so given the off‐grid electrification targets. Research has shown that off‐grid solar is increasingly showing a better cost‐benefit performance than grid‐based electrification in rural locations, therefore justifying its viability as a reasonable option to pursue (Grimm et al, ). Additionally, large‐scale grid extension program in Rwanda has seen an increase in the number of connections but the appliance uptake and energy consumption have remained low (Lenz et al, ), which provides another proof for the viability of utilizing solutions such as SHSs.…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 99%
“…Solar lanterns and Solar Home Systems (SHSs) have become some of the most prominent among standalone off‐grid solutions, which also include bioenergy, geothermal, hydro, and wind (Adil & Ko, ; International Renewable Energy Agency, ; Practical Action, ; Scott & Miller, ). Even though their capacities rarely go beyond 100 W, they offer clear benefits to the end users, improving the quality of life by eliminating harmful smoke, extending light hours, and thus productive time for income generation, allowing children to study longer, family members to charge their phones at home and getting access to information via radios and televisions (TVs)—all at a cost comparable to that of previous expenses on alternative sources (Global Off‐Grid Lighting Association [GOGLA], ; Grimm, Lenz, Peters, & Sievert, ). Given the capital intensive nature of DRE that requires heavy up‐front investment (Sovacool, ), increased participation of the private sector in the planning and provision of off‐grid solutions has begun to play an important role in places such as East Africa, Bangladesh, and India, with other regions following suit.…”
Section: Introductionmentioning
confidence: 99%